INTERRELATION OF METABOLIC SYNDROME COMPONENTS WITH CELL AND VESSEL AGING PARAMETERS - I. D. Strajesko; O. N. Tkacheva; D. U. Akasheva; E. V. Dudinskaya; M. V. Agaltsov; A. S. Kruglikova; N. V. Brailova; V. S. Pykhtina; E. V. Plokhova; O. Yu. Isaykina; V. A. Vygodin; N. V. Gomyranova; et al. (Российский кардиологический журнал)
Aim. To study the interrelation of different MS components and parameters of cell and vessel aging.Material and methods. Totally 136 patients studied with the age 25-75 y. without any signs of CVD or other chronic diseases, not receiving any continuous drug therapy. In all patients the antropometric parameters, BP levels, fasting plasma glucose, HDL cholesterol and triglycerides levels were measured. The PWV measurement was performed by the device SphygmoCor (AtCorMedical, Australia). Telomere length (TL) was measured by PCR.Results. Multidimensional regression analysis revealed that among all MS risk factors studied only the age (р=0,0003), waist circumference (р=0,0434), systolic BP (р=0,0001), НОМА-IR (р=0,0033), fasting glycemia (р=0,0001) and TL (р=0,0001) are the independent determinants of PWV, and this relation is reversed for TL, but direct — with the other parameters. Independent reversed relation is with TL only for age (р=0,0033) and НОМА-IR (р=0,0027).Concluson. Arterial hypertension can be named as the main hemodynamic component and impaired carbohydrate metabolism, insulin resistance and obesity as the main non-hemodynamic components of vessel wall rigidity increase and as the main target for therapeutical intervention.